PELATIHAN PEMBUATAN WEBSITE DAN DIGITAL MARKETING BAGI KARANG TARUNA DALAM MENINGKATKAN PEMASARAN PRODUK LOKAL - Afif Rizky, Andika; Suhendi, Agus; Aldi Aulia Fathurohman, Muhammad (Tensile : Jurnal Pengabdian Kepada Masyarakat, 2026)
Program Kemitraan Masyarakat (PKM) aims to enhance digital literacy and promotional capacity of the Karang Taruna youth organization through training in website development and digital marketing. The main problems faced by the partner include low understanding of digital technology, limited access to technology, and a lack of skills in marketing local products online. The activities were carried out at the Karang Taruna of Komplek Lebak Tirta and involved active members engaged in economic activities. The implementation methods included literature review, needs assessment, material preparation, theoretical and hands-on training, and post-activity mentoring. The results showed an improvement in participants’ skills in creating and managing websites integrated with social media, as well as readiness to use these platforms to promote local products. Participants were trained to create product landing pages, fill in visual content, integrate social media links (Instagram, Facebook, WhatsApp), and register their businesses on Google Maps and Google My Business. One example of implementation used in the training was the landing page for Sate Bandeng Khas Banten. The evaluation was conducted using a User Acceptance Test (UAT) to assess the quality and functionality of the websites created by participants. The UAT results showed that 85% of participants achieved a "Good" to "Very Good" rating, with functional and informative websites ready to be used as digital promotional media. This activity is expected to be the starting point for the digital transformation of Karang Taruna and the development of a sustainable technology-based community empowerment ecosystem